Lawrence W. Beer (ed.), Constitutional Systems in Late Twentieth Century Asia, Seattle y Londres, University of Washington Press, 1992, 740 pp. (Asian Law Series, School of Law, University of Washington, núm. 12) - M. Ch., R. (El Colegio de México, 1993)
-